PEMANFAATAN LIMBAH TANDAN KOSONG SAWIT (FLY ASH) UNTUK MENINGKATKAN KELIMPAHAN FITOPLANKTON PADA MEDIA BUDIDAYA - Niken Ayu Pamukas; Syafriadiman Syafriadiman; Mulyadi Mulyadi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2012)
Main problems facing by fish farmers in utilizing of swampy soil as otheralternatives for fish culture area are water and soil quality such as low soil andwater pH, uncertainty water supply, land topography and lack of nutrient content.In order to increase nutrient content in swampy soil, it should give manure. FlyAsh consist of P : 10.0-12.3 g/kg, K : 16.0-65.8 g/kg, Ca : 26.6-32.1 g/kg, Mg : 24.4-30.8 g/kg, Cu : 0.16-1.26 g/kg, dan B : 0.20-0.27 g/kg. Fly Ash an alternative thatcould be used in nutrient recycling or to return nutrient content on land.Application of fly ash could improve swampy soil and adding nutrient content forplant. The aim of this research was to investigate the effect of palm fly ashaddition on phytoplankton growth. Complete Random Design with one factor,four treatments and three replications was applied. Results showed that there waspositive relationship between concentration of fly ash and phytoplanktonabundance. Fly ash concentrations applied were: P0 (without fly ash), P1 (246.1g/m2), P2 (492.2 g/m2) and P3 (738.3 g/m2). Results shown that the bestphytoplankton abundance was obtained from P3 (738.3 g/m2) with phytoplanktonabundance was 2,945 cell/ml, while the worst was P0 (without fly ash) withphytoplankton abundance 1442 cel/ml. 17 species of phytoplankton were inventedin the research consist of 5 species of Chlorophyceae, 4species ofCyanophyceae, and 8 species of Bacillariophyceae respectively. The organicmaterial of soil content from 60.40-89.75 %, nitrate concentration 0.129-0.841ppm, temperature 26-35oC, water pH 5-9, turbidity 1-17 NTU, DO 2.1-4.5 ppm,CO2 11.99-46.57 ppm, orthoposphate concentration 0.079-0.524 ppm, hardness17.00-29.67 ppm.